Model Pembelajaran Pendidikan Agama Islam di Program Sarjana Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Aswar Harahap (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2024)
Abstract The bad quality of schooling in Indonesia is a well-established conversation. In any case, as of recently the issue of the nature of training is likewise wrapped up. Quality schooling is the assumption and request of all partners in training. Everybody will unquestionably really like to request science at an organization that has a decent quality. On this premise, schools/instructive organizations ought to have the option to offer great assistance and quality together not to be deserted and incapable of rivaling other instructive foundations. From different perspectives, rules, and markers that we can take that quality instruction could be improved assuming the school has one) support from the public authority, 2) Administration Chiefs compelling, 3) Execution great educators, 4) an important educational program 5) graduates quality, 6) culture and environment of viable association, 7) the help of the local area and guardians. Execution of the board in working on the nature of schooling is a genuine arrangement to be trusted to deal with the signs of the nature of training to make cooperative energy in endeavors to work on the nature of instruction.Keywords: Quality Improvement, Education Quality Management